Primary human polarized small intestinal epithelial barriers respond differently to a hazardous and an innocuous protein. (August 2017) - Eaton, A.D.; Zimmermann, C.; Delaney, B.; Hurley, B.P.
Abstract: An experimental platform employing human derived intestinal epithelial cell (IEC) line monolayers grown on permeable Transwell ® filters was previously investigated to differentiate between hazardous and innocuous proteins. This approach was effective at distinguishing these types of proteins and perturbation of monolayer integrity, particularly transepithelial electrical resistance (TEER), was the most sensitive indicator. In the current report, in vitro indicators of monolayer integrity, cytotoxicity, and inflammation were evaluated using primary (non-transformed) human polarized small intestinal epithelial barriers cultured on Transwell ® filters to compare effects of a hazardous protein ( Clostridium difficile Toxin A [ToxA]) and an innocuous protein (bovine serum albumin [BSA]). ToxA exerted a reproducible decrease on barrier integrity at doses comparable to those producing effects observed from cell line-derived IEC monolayers, with TEER being the most sensitive indicator. In contrast, BSA, tested at concentrations substantially higher than ToxA, did not cause changes in any of the tested variables. These results demonstrate a similarity in response to certain proteins between cell line-derived polarized IEC models and a primary human polarized small intestinal epithelial barrier model, thereby reinforcing the potential usefulness of cell line-derived polarized IECs as a valid experimental platform to differentiate between hazardous and non-hazardous proteins. Highlights: Integrity of primary small intestinal epithelial cell barriers was decreased when cells were exposed to C. difficile Toxin A. TEER was the most sensitive indicator of decreased barrier integrity. No effect was observed when primary small intestinal barriers were exposed to bovine serum albumin (BSA). Primary small intestinal barriers and cell line-derived intestinal epithelial barriers react to ToxA and BSA similarly.